2013
DOI: 10.2967/jnumed.113.125476
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Prostate-Specific Membrane Antigen Liposomes Loaded with225Ac for Potential Targeted Antivascular α-Particle Therapy of Cancer

Abstract: This study evaluates targeted liposomes loaded with the a-particle generator 225 Ac to selectively kill prostate-specific membrane antigen (PSMA)-expressing cells with the aim to assess their potential for targeted antivascular radiotherapy. Methods: In this study, PEGylated liposomes were loaded with 225 Ac and labeled with the mouse antihuman PSMA J591 antibody or with the A10 PSMA aptamer. The targeting selectivity, extent of internalization, and killing efficacy of liposomes were evaluated on monolayers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…The use of active targeting radionuclide nanoparticles in internal radiotherapy has been successfully employed to image and treat tumor models preclinically. These radionuclide nanoparticles include human atherosclerotic plaque-specific peptide-1-targeted 111 In-labeled liposomes (Yang et al 2012), monoclonal antinuclear autoantibody 2C5 (mAb 2C5) targeting 111 In-immunoliposome for lung carcinoma (Elbayoumi et al 2007), α v β 3 -integrintargeted 111 In perfluorocarbon nanoparticles for targeted tumor imaging (Hu et al 2007), rituximab targeting 111 In carbon nanotubes for targeted tumor imaging (McDevitt et al 2007), RGD-or VEGF-targeted 64 Cu quantum dots or iron oxide for PET/NIRF and PET/MRI imaging Lee et al 2008), EGFR-targeted 99m Tc-chelated quantum dots for breast cancer imaging and therapy (Jung et al 2011), RGD-targeted 125 I-labeled gold nanoparticles for tumor imaging (Kim et al 2011), HER2-targeted nanoparticles loaded with an 125 I-labeled DNA intercalator (Fondell et al 2011), anti-prostate-specific membrane antigen nanoparticles loaded with 225 Ac for potential targeted anti-vascular α-particle therapy (Bandekar et al 2014), 76 Br-labeled RGD-directed-dendritic nanoprobes for PET imaging (Almutairi et al 2009), and integrin antagonist or anti-Flk-1 antibody-coated 90 Y-labeled nanoparticles (Li et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The use of active targeting radionuclide nanoparticles in internal radiotherapy has been successfully employed to image and treat tumor models preclinically. These radionuclide nanoparticles include human atherosclerotic plaque-specific peptide-1-targeted 111 In-labeled liposomes (Yang et al 2012), monoclonal antinuclear autoantibody 2C5 (mAb 2C5) targeting 111 In-immunoliposome for lung carcinoma (Elbayoumi et al 2007), α v β 3 -integrintargeted 111 In perfluorocarbon nanoparticles for targeted tumor imaging (Hu et al 2007), rituximab targeting 111 In carbon nanotubes for targeted tumor imaging (McDevitt et al 2007), RGD-or VEGF-targeted 64 Cu quantum dots or iron oxide for PET/NIRF and PET/MRI imaging Lee et al 2008), EGFR-targeted 99m Tc-chelated quantum dots for breast cancer imaging and therapy (Jung et al 2011), RGD-targeted 125 I-labeled gold nanoparticles for tumor imaging (Kim et al 2011), HER2-targeted nanoparticles loaded with an 125 I-labeled DNA intercalator (Fondell et al 2011), anti-prostate-specific membrane antigen nanoparticles loaded with 225 Ac for potential targeted anti-vascular α-particle therapy (Bandekar et al 2014), 76 Br-labeled RGD-directed-dendritic nanoprobes for PET imaging (Almutairi et al 2009), and integrin antagonist or anti-Flk-1 antibody-coated 90 Y-labeled nanoparticles (Li et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…has been conjugated to doxorubicin micelles, which led to an increased uptake by PSMA-positive CWR22R-nu1 prostate cancer cells and resulted in higher cytotoxicity than that achieved using nontargeting micelles (25). More recently, a similar strategy was used in constructing 225 Ac-loaded liposomes to target and selectively kill PSMA-expressing cells such as LNCaP, Mat-Lu, and HUVEC using radiation (26). However, aptamers utilized in these studies were selected on the basis of binding to isolated surface markers or recombinant proteins, which might poorly reflect the native protein conformations owing to denaturing conditions during purification (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In cytotoxicity studies against human umbilical vein en-dothelial cells that were induced to express human PSMA, Bandekar et al (104) demonstrated that targeted liposomes exhibited comparable median lethal dose values to the values measured for the radiolabeled J591 antibody.…”
Section: Preclinical α-Particle Therapy Delivered By Nanometer-sizmentioning
confidence: 99%